1986
DOI: 10.1002/1097-0355(198621)7:1<19::aid-imhj2280070104>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Early stress and social support influences on mothers' and high-risk infants' functioning in late infancy

Abstract: The relationships among early stress, maternal social network supports, and mother‐infant functioning during later infancy were explored in a group of 52 mothers and their high‐risk premature infants. Maternal stress and support data were collected 1 month after infants were released from the hospital, and measures of parenting, mother‐infant interaction, infant social and developmental competence, and infant attachment were collected at infant corrected ages of 8 and 12 months. Results indicated that stress a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
3

Year Published

1986
1986
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(59 citation statements)
references
References 30 publications
5
50
0
3
Order By: Relevance
“…In addition, the data suggested that more social support from other women is directly related to greater infant attachment security. This finding is consistent with those of several previous studies (Crittenden, 1985;Crnic et al, 1986;Crockenberg, 1981); however, the current study is the first to show this relationship for female support specifically. This direct association may be due to: (a) exposure to positive models of caregiving, which women then repeat with their own children; (b) corrective attachment experiences that alter working models or improve mothers' abilities to be sensitively attuned to their infants; or (c) mothers' generalized working models of relationships, which influence their choice of female supporters and their perceptions of and relationships with their infants.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, the data suggested that more social support from other women is directly related to greater infant attachment security. This finding is consistent with those of several previous studies (Crittenden, 1985;Crnic et al, 1986;Crockenberg, 1981); however, the current study is the first to show this relationship for female support specifically. This direct association may be due to: (a) exposure to positive models of caregiving, which women then repeat with their own children; (b) corrective attachment experiences that alter working models or improve mothers' abilities to be sensitively attuned to their infants; or (c) mothers' generalized working models of relationships, which influence their choice of female supporters and their perceptions of and relationships with their infants.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, low social support had a greater impact on attachment with irritable babies than with easy babies, suggesting the importance of support in more stressed families. Several other studies have also reported that social support positively affected infant -mother attachment security (Crittenden, 1985;Crnic, Greenberg, & Slough, 1986;Spieker & Booth, 1988), with each study defining social support differently. Stern (1995), in particular, asserted that support from other women, many of whom have likely been mothers, may be especially important at this time in a woman's life because of the increased credibility granted to them as a result of their own experiences with caregiving.…”
Section: Contextual Variables and Infant -Mother Attachmentmentioning
confidence: 97%
“…Social support was assessed at week 12. The social support measure (Henderson, Byrne & Duncan-Jones, 1981;Crnic, Greenberg, Ragozin, Robinson & Basham, 1983;Crnic, Greenberg & Slough, 1986) has previously been used in Swedish research on mother± infant functioning (Lindberg, Bohlin, Hagekull & Thunstrom, 1994). The wording on 5 of the 10 items was adapted to focus on the pregnancy' s effect on relationships, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Studies by Davis and Windle (1997) and Fergusson et al (1995) both supported that parental psychological distress was related to marital discord and spousal conflict by disagreements and withdrawal of mutual support between the couple. Accordingly, it is in the same vein with other research, heightened parental stress would undermine family functioning (Sepa et al, 2004;Crnic et al, 1986).…”
Section: The Mediating Role Of Parents' Psychological Health In Familmentioning
confidence: 58%